The Red Rose Box - Woods, Brenda (Brenda A.) (New York : G.P. Putnam's Sons, 2002)
In 1953, Leah Hopper dreams of leaving the poverty and segregation of her home in Sulphur, Louisiana, and when Aunt Olivia sends train tickets to Los Angeles as part of her tenth birthday present, Leah gets a first taste of freedom.
Keywords: Segregation -- Fiction; African Americans -- Fiction; Sisters -- Fiction; Louisiana -- Fiction; Los Angeles (Calif.) -- Fiction